BIM approach to modeling a sports pavilion for university use - Nuñez Muñoz, Juan (2021)
New developments in software projects for the construction sector are a technological revolution and provide new methods of infrastructure design and modeling, highlighting the Building Information Modeling (BIM). BIM is a technology and methodology used in the most developed countries and little by little this technology is being implemented in other countries where its use is increasing. This new work methodology makes it easier to manage and plan new projects, saving time and minimizing costs. The advantages of using BIM stand out in large projects thanks to the better handling of large volumes of information. This article will address, with the example of using BIM technology, the design project of a fictitious university sports pavilion located in Seville (Spain). Using the BIM Edificius® software, the 3D modeling of this building will be carried out in order to calculate and design the building’s facilities with CYPECAD MEP® software, making use of the IFC (Industry Foundation Classes) format to exchange the building design between both programs.